Spherical fuzzy decision support approach to evaluate the sustainable strategies in agri-food supply chains: A case study in tea supply chain - Yildirim, Betul; Ayyildiz, Ertugrul; Aydin, Nezir (ELSEVIER, 2025)
This study proposes a novel sustainability-focused model for evaluating agri-food supply chains, illustrated by a Turkish tea supply chain case ensuring environmental, economic, and social benefits. The research aims to assess and prioritize strategies for enhancing sustainability by identifying key criteria within the sustainability framework. We identify and weigh comprehensive environmental, social, economic, and technical criteria, then rank five strategies aimed at long-term resilience and efficiency. Findings reveal low R&D investment as a major barrier while adopting digital technologies emerges as the most effective solution. These results highlight the novelty of sustainability in our framework, guiding stakeholders toward more balanced decisions.
Keywords: Sustainable agriculture; Agri-food supply chain; Decision-making; Tea supply chain; Spherical fuzzy sets; Tea production in T & uuml; rkiye; MANAGEMENT; GREEN; FRAMEWORK; PERFORMANCE; SELECTION; PRODUCTS; DESIGN; Environmental Sciences & Ecology; Operations Research & Management Science